Snakelike metal-elastomer composite transparent conductive film, design and fabrication method and application thereof

CN122968039APending Publication Date: 2026-10-23NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611380113.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,关于最优圆心角数值的系统研究至今仍较为缺乏

Benefits of technology

[0013]与现有技术相比,本发明的有益效果至少包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968039A_ABST
    Figure CN122968039A_ABST
Patent Text Reader

Abstract

The application provides a serpentine metal-elastomer composite transparent conductive film, a design and manufacturing method and application thereof. The conductive film comprises a transparent elastomer film and an embedded metal mesh, the embedded metal mesh comprises first serpentine lines and a plurality of second serpentine lines, and each of the first serpentine lines and the second serpentine lines is composed of super-semi-circular arcs arranged alternately on both sides of a center line, and the intersection point is the end point of the super-semi-circular arcs. The serpentine metal-elastomer composite transparent conductive film provided by the application adopts super-semi-circular arcs to form the longitudinal and transverse lines of the embedded metal mesh, compared with the 180° semi-circular lines and sinusoidal lines in the prior art, the serpentine metal-elastomer composite transparent conductive film can provide more stretching allowance and greatly improve the cyclic deformation stability; according to the design method provided by the application, balance can be achieved among the interface peeling, fatigue stability, cycle life and conductive performance, the super-semi-circular arc central angle interval and radius with the best comprehensive performance are obtained, and the corresponding structure design is efficiently guided to output the optimal result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flexible electronics technology, specifically relating to a serpentine metal-elastomer composite transparent conductive film, its design, fabrication method, and application. Background Technology

[0002] With the rapid development of flexible electronics, cutting-edge applications such as wearable smart devices, flexible displays, bionic electronic skin, and implantable biomedical devices urgently require transparent conductive electrodes that combine high electrical conductivity, high optical transmittance, and the ability to withstand significant mechanical deformation. While traditional indium tin oxide (ITO) films possess high conductivity (thin-film resistance can be as low as approximately 10 Ω / sq) and high visible light transmittance (>90%), their inherent brittleness due to their ceramic properties means that even under minute bending or tensile strain (typically <2%), microcracks will initiate and rapidly propagate within the film, ultimately leading to the breakage of the conductive path, a sharp increase in resistance, or even open circuit, causing catastrophic device failure. This fundamentally limits the application of ITO in flexible and stretchable electronic products requiring large deformation capabilities.

[0003] To overcome the rigidity limitations of materials such as ITO, academia and industry have explored various alternative material systems. Conductive polymers (such as PEDOT:PSS), while possessing intrinsic flexibility, suffer from low conductivity and are susceptible to performance degradation due to humidity. Carbon-based nanomaterials (carbon nanotubes, graphene) exhibit excellent mechanical and electrical properties, but their large-area uniform film formation process is complex, and the interfacial contact resistance between nanostructure units significantly restricts the improvement of macroscopic conductivity. Metal nanowire networks (such as silver nanowires) achieve a better balance between conductivity and transparency, but suffer from high light haze, susceptibility of nanowire nodes to failure under electro-thermal-mechanical coupling, and poor adhesion to flexible substrates, limiting their long-term reliability. In summary, the above solutions struggle to balance conductivity, transparency, mechanical flexibility, and large-scale manufacturing costs, and have not yet formed an optimal solution that meets the needs of practical applications.

[0004] In recent years, the metal mesh technology approach based on structural mechanics design has demonstrated unique advantages. This strategy utilizes geometric deformation (unfolding, bending, and rotation) to absorb strain by constructing periodic geometric configurations (such as serpentine, honeycomb, and fractal structures) with highly conductive metals (such as copper, silver, and gold), rather than relying on the lattice stretching of the material itself. This allows macroscopic tensile strain to reach 100% or even higher, while the actual strain experienced by the metal lines is far below the fracture limit, thus perfectly preserving the inherent high electrical conductivity of the metal material while maintaining excellent tensile strength. However, existing serpentine structure designs mostly adopt traditional 180° semicircular arcs or sinusoidal wave configurations, and their geometric parameters (such as central angle and arc radius) have not been systematically optimized. Taking a 180° semicircular arc as an example, after 300 cycles at 20% strain, the normalized resistance change (ΔR / R0) is approximately 0.7; the ΔR / R0 of a sinusoidal serpentine structure even exceeds 2.8 under the same conditions. These data indicate that there is still significant room for improvement in the cyclic tensile stability of existing geometries, especially in high-frequency deformation scenarios (such as wearable sensors and bionic electronic skin), where resistance drift becomes the core bottleneck restricting long-term reliability.

[0005] From a structural mechanics perspective, the central angle of a serpentine structure is a key geometric parameter determining the uniformity of strain distribution and the degree of local stress concentration. Under tension, the traditional 180° semicircular arc has limited unfolding margin, with strain mainly concentrated at the junction of the arc and the straight section. This leads to the initial accumulation of plastic strain in this region during cyclic tension, ultimately causing micromesh fracture or deintercalation failure. Theoretically, increasing the central angle (e.g., using a super-semicircular arc configuration, i.e., a central angle > 180°) can provide a larger arc length reserve, resulting in a more uniform strain distribution and significantly improved cyclic stability. However, systematic research on the optimal central angle value remains relatively lacking.

[0006] Furthermore, the radius of curvature (or characteristic scale) of the serpentine micromesh directly affects the trade-off between optical transmittance and tensile stability. A smaller radius of curvature (e.g., 50 μm) means a higher metal line density per unit area, which not only reduces transmittance but also provides denser geometric units, leading to more fracture points and hindering improved cycle stability. Conversely, a larger radius of curvature (e.g., 350 μm) can significantly improve transmittance (approaching 90%), reduce the number of geometric units, and improve cyclic tensile performance. Achieving a flexible trade-off between transmittance and tensile stability through multi-scale radius control strategies is crucial to meeting the needs of different application scenarios.

[0007] In summary, two core scientific problems urgently need to be addressed: (1) optimizing the design of the central angle of the serpentine structure to maximize cyclic stretching stability; and (2) developing a multi-scale arc radius control strategy to achieve a flexible balance between transmittance and stretching performance. Simultaneously, it is necessary to develop a short-process, low-cost fabrication process to stably and reliably fabricate high-performance serpentine copper micromesh transparent conductive films directly on flexible substrates. Such technological breakthroughs will not only solve common problems in the current field of flexible electronics but will also pave the way for the implementation of disruptive technologies such as wearable medical devices, human-computer interfaces, and flexible displays, thus possessing significant practical implications and broad market prospects. Summary of the Invention

[0008] The main objective of this invention is to provide a serpentine metal-elastomer composite transparent conductive film, its design, manufacturing method, and application, so as to overcome the shortcomings of the prior art.

[0009] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a serpentine metal-elastomer composite transparent conductive film, comprising a transparent elastomer film and an embedded metal mesh, wherein the embedded metal mesh comprises a plurality of crisscrossing first serpentine lines and a plurality of second serpentine lines, wherein the first serpentine lines and the second serpentine lines are each composed of alternating semi-circular arcs arranged on both sides of a center line, and the intersection of the first serpentine lines and the second serpentine lines is the endpoint of the semi-circular arc.

[0010] Secondly, the present invention also provides a design method for the above-mentioned serpentine metal-elastomer composite transparent conductive film, comprising: The range of central angle values ​​for the serpentine lines in the serpentine metal-elastomer composite transparent conductive film is determined by using constraints, including: Interface stripping constraints: (E_m·t·ε0 2 ) / (E_s·t_s·2.16)·sin 2 (θ / 2)·[1+cos 2 (θ / 2)]·[1+0.25·K_stress(θ)]≤8·G_c; Fatigue stability constraints: 2·ε0·sin 2 (θ / 2)·[1+K_stress(θ) / 10]·K_stress(θ)<6.0; Geometric constraints: 180° < θ < 270°; Resistance constraint: ρ·L_eff / (w·t)≤100Ω; Fatigue life constraints: N_f(θ)≥10 4 ; in: K_stress(θ)=1+2.8·|sin(θ-180°)|^1.5·[1+0.45·(t / w)^0.6]·[1+0.08·(E_m / E_s)^0.3]; G_IC,plastic(θ)=(E_m·t·ε0²) / (E_s·t_s·2.16)·sin²(θ / 2)·[1+cos²(θ / 2)]·[1+0.25·K_stress(θ)]; L_eff(θ) / L0=2(πR·α / 180°+l) / (2R+2l), R=w / [2·sin(α / 2)], α=θ-180°; N_f(θ) = 8 × 10 5 ·[Δε_eff(θ)]^(-1.8), Δε_eff(θ)=2·ε0·sin²(θ / 2)·[1+K_stress(θ) / 10]; E_m represents the elastic modulus of the embedded metal mesh, t represents the thickness of the first and second serpentine lines, ε0 represents the design strain, E_s represents the elastic modulus of the transparent elastomer film, t_s represents the thickness of the transparent elastomer film, θ represents the central angle, α represents the deflection angle, K_stress(θ) represents the stress concentration factor, G_c represents the interfacial fracture energy, ρ represents the resistivity of the embedded metal mesh, G_IC,plastic(θ) represents the interfacial energy release rate related to the central angle, L_eff represents the effective tensile length, L0 represents the straight length of the serpentine lines, w represents the planar pattern width of the first and second serpentine lines, N_f represents the fatigue life; Δε_eff represents the effective strain amplitude. Within the range of values, the final value of the central angle is determined.

[0011] Thirdly, the present invention also provides a method for preparing the above-mentioned serpentine metal-elastomer composite transparent conductive film, comprising: A metal seed layer is set on the substrate surface; A patterned mask layer is disposed on the surface of the metal seed layer, the pattern of the mask layer being complementary to the pattern of the embedded metal mesh; The embedded metal mesh is formed by depositing on the metal seed layer exposed in the mask layer using electrochemical deposition. Remove the mask layer, and cast and cure to form a transparent elastomer film; The transparent elastomer film and the serpentine metal-elastomer composite transparent conductive film formed by the embedded metal mesh are peeled off from the metal seed layer.

[0012] Fourthly, the present invention also provides the application of the above-mentioned serpentine metal-elastomer composite transparent conductive film in the fabrication of wearable smart devices, flexible displays, biomimetic electronic skin, and implantable biomedical devices.

[0013] Compared with the prior art, the beneficial effects of the present invention include at least the following: The serpentine metal-elastomer composite transparent conductive film provided by this invention uses ultra-semi-circular arcs to form the longitudinal and transverse lines embedded in the metal grid. Compared with the 180° semi-circular lines and sine wave lines in the prior art, it can provide more stretching allowance and greatly improve the stability of cyclic deformation. According to the design method provided by this invention, a balance can be achieved between interface stripping, fatigue stability, cycle life and conductivity, and the optimal range of semi-circular arc central angle and radius with comprehensive performance can be obtained, which can efficiently guide the corresponding structural design to output the optimal results.

[0014] The above description is merely an overview of the technical solution of the present invention. In order to enable those skilled in the art to better understand the technical means of this application and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described below in conjunction with detailed drawings. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic diagram of the preparation process of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention; Figure 2a This is a design morphology diagram of a metal-elastomer composite transparent conductive film provided in a typical embodiment and comparative case of the present invention; Figure 2b This is a radar chart comparing the performance of a metal-elastomer composite transparent conductive film provided in a typical embodiment and comparative case of the present invention. Figure 2c This is a comparative test chart of the optical transmittance of a metal-elastomer composite transparent conductive film provided in a typical embodiment and comparative case of the present invention. Figure 2dThis is a comparative test chart of the tensile cycle stability of a metal-elastomer composite transparent conductive film under 20% strain, provided in a typical embodiment and comparative case of the present invention. Figure 3a This is a design morphology diagram of a multi-scale serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 3b This is a test diagram showing the resistivity change of a multi-scale serpentine metal-elastomer composite transparent conductive film under 20% stretching, provided in a typical embodiment of the present invention. Figure 3c This is a comparative test diagram of the photoelectric performance of a multi-scale serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 3d This is a comparative test chart of the optical transmittance of a multi-scale serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 3e This is an SEM image of a 350-micron large-size serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 4a This is a uniformity verification photograph of the serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 4b This is a uniformity verification test diagram of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 4c This is a practical application demonstration (LED lighting test) of the serpentine metal-elastomer composite transparent conductive film under different tensile strains provided in a typical embodiment of the present invention. Figure 4d This is a typical embodiment of the present invention, showing the change in resistance of a serpentine metal-elastomer composite transparent conductive film under different strains after 100 tensile tests. Figure 4e This is a data graph of the long-cycle cyclic bending (5mm) stability test (10,000 cycles) of the serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 4f This is a graph showing the stability test (5000 cycles) of a serpentine metal-elastomer composite transparent conductive film under ultra-long cycle stretching of 20%. Figure 4g This is a comparative test chart of the cyclic tensile resistivity change of the serpentine metal-elastomer composite transparent conductive film under different electroplating times, provided in a typical embodiment of the present invention. Figure 5aThis is a top-view low-magnification SEM image of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 5b This is a top-view low-magnification SEM image of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 5c This is a top-view high-magnification SEM image of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 5d This is an X-ray diffraction (XRD) pattern of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention; Figure 5e This is a SEM image of a repeating unit of a serpentine metal-elastomer composite transparent conductive film provided in a typical embodiment of the present invention. Figure 5f This is an image showing the distribution of repeating unit C elements in a serpentine metal-elastomer composite transparent conductive film, provided in a typical embodiment of the present invention. Figure 5g This is an image showing the Cu element distribution of a repeating unit in a serpentine metal-elastomer composite transparent conductive film, provided in a typical embodiment of the present invention. Figure 5h This is a typical embodiment of the present invention, showing the distribution of repeating unit O elements in a serpentine metal-elastomer composite transparent conductive film. Figure 5i This is an image showing the Si element distribution of the repeating unit of a serpentine metal-elastomer composite transparent conductive film, provided in a typical embodiment of the present invention. Detailed Implementation

[0017] In view of the shortcomings of the prior art, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention. The following will further explain and illustrate this technical solution, its implementation process, and its principles.

[0018] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0019] The main technical problems to be solved by this invention include: I. Poor Cyclic Stability of Existing Stretchable Transparent Electrodes: Traditional silver / copper nanowire-PDMS composite electrodes have high contact resistance at the nanowire overlap. After stretching by more than 20%, the resistance increases by more than 100%. During cyclic stretching, the nanowires are prone to slippage, resulting in severe resistance drift, which cannot meet the requirements for long-term use.

[0020] II. The geometric design of traditional serpentine structures is not optimized, resulting in limited stability under cyclic stretching: Existing serpentine structures (such as 180° arcs and sine waves) have insufficient performance under cyclic stretching: After 300 cycles at 20% strain, the sine wave serpentine structure has ΔR / R0>2.8; the 180° arc structure has ΔR / R0≈0.7 under the same conditions. Neither of these can meet the long-term stable use requirements of high-frequency deformation scenarios (such as wearable sensors and electronic skin).

[0021] Third, it is difficult to balance light transmittance and tensile stability: existing solutions often fall into the dilemma of "high light transmittance-low stability" or "high stability-low light transmittance", lacking a systematic scale control strategy to achieve a flexible trade-off in performance.

[0022] IV. The fabrication process of high-precision metal micromesh has problems such as high cost, complex process or difficulty in integration with flexible substrate: laser direct writing, inkjet printing and other methods have poor line width accuracy (>100 μm) and expensive equipment; transfer method is prone to defects such as breakage and wrinkles during mechanical peeling, resulting in low device yield and poor performance consistency.

[0023] This invention first provides a serpentine metal-elastomer composite transparent conductive film, which includes a transparent elastomer film and an embedded metal mesh. The embedded metal mesh includes a plurality of crisscrossing first serpentine lines and a plurality of second serpentine lines. Both the first serpentine lines and the second serpentine lines are composed of alternating semi-circular arcs arranged on both sides of the center line, and the intersection of the first serpentine lines and the second serpentine lines is the endpoint of the semi-circular arc.

[0024] In some implementations, the central angle of the super-semicircular arc is 180-270°.

[0025] In this invention, the stretchable transparent conductive film refers to a functional film that maintains high conductivity (low sheet resistance), high optical transmittance, and structural integrity even under mechanical deformations such as stretching, bending, and twisting. It is a core component of flexible electronic devices (such as wearable sensors, flexible displays, and electronic skin). The three-dimensional embedded structure refers to a metal conductive microgrid completely embedded within an elastic polymer substrate, with the elastomer forming a semi-enclosed covering of the metal structure along three sides, achieving structural anchoring rather than merely adhering to the surface. This structure significantly enhances the bonding force between the metal mesh and the substrate, preventing failure modes such as delamination and separation during cyclic stretching.

[0026] Based on the above technical solution, the present invention proposes a structural design with a super semi-circular arc serpentine shape at the central angle. Compared with the traditional 180° semi-circular arc, the super semi-circular arc segment has a larger arc length reserve within the same period, which can provide a larger geometric unfolding margin during stretching, effectively disperse local stress concentration, and fundamentally improve cyclic stretching stability.

[0027] Meanwhile, the embedded metal mesh is fully embedded in the transparent elastomer film rather than attached to the surface. The metal structure is semi-enclosed and anchored by the elastomer from three sides, preventing separation from the surface and significantly enhancing the bonding force.

[0028] In some implementations, the radius of the semicircular arc is 50-350 μm. By systematically adjusting the arc radius R (50-350 μm), a flexible trade-off between light transmittance (70%-92%@550nm) and tensile stability can be achieved to meet the needs of different application scenarios.

[0029] In some implementations, the constraints on the geometric properties of the embedded metal mesh include: Interface stripping constraints: (E_m·t·ε0 2 ) / (E_s·t_s·2.16)·sin 2 (θ / 2)·[1+cos 2 (θ / 2)]·[1+0.25·K_stress(θ)]≤8·G_c; Fatigue stability constraints: 2·ε0·sin 2 (θ / 2)·[1+K_stress(θ) / 10]·K_stress(θ)<6.0; Geometric constraints: 180° < θ < 270°; Resistance constraint: ρ·L_eff / (w·t)≤100Ω; Fatigue life constraints: N_f(θ)≥10 4 ; in: K_stress(θ)=1+2.8·|sin(θ-180°)|^1.5·[1+0.45·(t / w)^0.6]·[1+0.08·(E_m / E_s)^0.3]; G_IC,plastic(θ)=(E_m·t·ε0²) / (E_s·t_s·2.16)·sin²(θ / 2)·[1+cos²(θ / 2)]·[1+0.25·K_stress(θ)]; L_eff(θ) / L0=2(πR·α / 180°+l) / (2R+2l), R=w / [2·sin(α / 2)], α=θ-180°; N_f(θ) = 8 × 10 5·[Δε_eff(θ)]^(-1.8), Δε_eff(θ)=2·ε0·sin²(θ / 2)·[1+K_stress(θ) / 10]; E_m represents the elastic modulus of the embedded metal mesh, t represents the thickness of the first and second serpentine lines, ε0 represents the design strain, E_s represents the elastic modulus of the transparent elastomer film, t_s represents the thickness of the transparent elastomer film, θ represents the central angle, α represents the deflection angle, K_stress(θ) represents the stress concentration factor, G_c represents the interfacial fracture energy, ρ represents the resistivity of the embedded metal mesh, G_IC,plastic(θ) represents the interfacial energy release rate related to the central angle, L_eff represents the effective tensile length, L0 represents the straight length of the serpentine lines, w represents the planar pattern width of the first and second serpentine lines (not the width of the lines themselves), N_f represents the fatigue life; Δε_eff represents the effective strain amplitude.

[0030] In some embodiments, the material of the embedded metal mesh includes any one or a combination of two or more of Cu, Au, and Ni.

[0031] In some embodiments, the material of the transparent elastomer film includes any one or a combination of two or more of PDMS, PBAT, SEBS, and TPE.

[0032] This invention also provides a design method for the serpentine metal-elastomer composite transparent conductive film provided in any of the above embodiments, which includes the following steps: The range of central angle values ​​for the serpentine lines in the serpentine metal-elastomer composite transparent conductive film is determined by using constraints, including: Interface stripping constraints: (E_m·t·ε0 2 ) / (E_s·t_s·2.16)·sin 2 (θ / 2)·[1+cos 2 (θ / 2)]·[1+0.25·K_stress(θ)]≤8·G_c; Fatigue stability constraints: 2·ε0·sin 2 (θ / 2)·[1+K_stress(θ) / 10]·K_stress(θ)<6.0; Geometric constraints: 180° < θ < 270°; Resistance constraint: ρ·L_eff / (w·t)≤100Ω; Fatigue life constraints: N_f(θ)≥10 4 ; in: K_stress(θ)=1+2.8·|sin(θ-180°)|^1.5·[1+0.45·(t / w)^0.6]·[1+0.08·(E_m / E_s)^0.3]; G_IC,plastic(θ)=(E_m·t·ε0²) / (E_s·t_s·2.16)·sin²(θ / 2)·[1+cos²(θ / 2)]·[1+0.25·K_stress(θ)]; L_eff(θ) / L0=2(πR·α / 180°+l) / (2R+2l), R=w / [2·sin(α / 2)], α=θ-180°; N_f(θ) = 8 × 10 5 ·[Δε_eff(θ)]^(-1.8), Δε_eff(θ)=2·ε0·sin²(θ / 2)·[1+K_stress(θ) / 10]; E_m represents the elastic modulus of the embedded metal mesh, t represents the thickness of the first and second serpentine lines, ε0 represents the design strain, E_s represents the elastic modulus of the transparent elastomer film, t_s represents the thickness of the transparent elastomer film, θ represents the central angle, α represents the deflection angle, K_stress(θ) represents the stress concentration factor, G_c represents the interfacial fracture energy, ρ represents the resistivity of the embedded metal mesh, G_IC,plastic(θ) represents the interfacial energy release rate related to the central angle, L_eff represents the effective tensile length, L0 represents the straight length of the serpentine lines, w represents the width of the first and second serpentine lines, N_f represents the fatigue life; Δε_eff represents the effective strain amplitude. Within the range of values, the final value of the central angle is determined.

[0033] In some implementations, the design method specifically includes: Obtain the median value of the range; The intermediate value is rounded to obtain the final value.

[0034] This invention also provides a method for preparing the serpentine metal-elastomer composite transparent conductive film provided in any of the above embodiments, which includes the following steps: A metal seed layer is set on the substrate surface; A patterned mask layer is disposed on the surface of the metal seed layer, the pattern of the mask layer being complementary to the pattern of the embedded metal mesh; The embedded metal mesh is formed by depositing on the metal seed layer exposed in the mask layer using electrochemical deposition. Remove the mask layer, and cast and cure to form a transparent elastomer film; The transparent elastomer film and the serpentine metal-elastomer composite transparent conductive film formed by the embedded metal mesh are peeled off from the metal seed layer.

[0035] The above-mentioned preparation method involves in-situ growth of an embedded metal mesh through photolithography and electroplating, followed by casting a thin film for overall encapsulation, and finally peeling off to achieve non-destructive transfer. This avoids defects such as breakage and wrinkles introduced during the peeling process in transfer printing methods. The device yield is high, the performance consistency is good, and the process only requires conventional photolithography / electroplating / casting with a copper line width of about 5 μm. It does not require expensive equipment such as laser direct writing or nanoimprinting. Mechanical peeling does not require etching solution, further reducing costs.

[0036] In some embodiments, the preparation method specifically includes: The serpentine metal-elastomer composite transparent conductive film is mechanically peeled off from the metal seed layer; Alternatively, an etchant can be dropped onto the edge of the serpentine metal-elastomer composite transparent conductive film and the metal seed layer for chemical stripping.

[0037] This invention also provides the application of the serpentine metal-elastomer composite transparent conductive film provided in any of the above embodiments in the fabrication of wearable smart devices, flexible displays, biomimetic electronic skin, and implantable biomedical devices.

[0038] The technical solution of the present invention will be further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only for illustrating the present invention and do not limit the scope of the present invention.

[0039] Example 1 This embodiment illustrates the structural design process of a copper microgrid embedded with a PDMS composite transparent conductive film, focusing on the design of its optimal central angle, as shown below: Multiple constraints are used to limit the range of the central angle, including: C1. Interface stripping constraint: (E_m·t·ε0 2 ) / (E_s·t_s·2.16)·sin 2 (θ / 2)·[1+cos 2 (θ / 2)]·[1+0.25·K_stress(θ)]≤8·G_c; C2. Fatigue stability constraint: 2·ε0·sin 2(θ / 2)·[1+K_stress(θ) / 10]·K_stress(θ)<6.0; Geometric constraints: 180° < θ < 270°; C3. Angle range constraint: 180° < θ < 270° C4. Resistance constraint: ρ·L_eff / (w·t)≤100Ω; C5. Fatigue life constraint: N_f(θ)≥10 4 ; in: K_stress(θ)=1+2.8·|sin(θ-180°)|^1.5·[1+0.45·(t / w)^0.6]·[1+0.08·(E_m / E_s)^0.3]; G_IC,plastic(θ)=(E_m·t·ε0²) / (E_s·t_s·2.16)·sin²(θ / 2)·[1+cos²(θ / 2)]·[1+0.25·K_stress(θ)]; L_eff(θ) / L0=2(πR·α / 180°+l) / (2R+2l), R=w / [2·sin(α / 2)], α=θ-180°; N_f(θ) = 8 × 10 5 ·[Δε_eff(θ)]^(-1.8), Δε_eff(θ)=2·ε0·sin²(θ / 2)·[1+K_stress(θ) / 10].

[0040] For copper microgrids and PDMS thin film materials, the meanings and values ​​of the symbols in the above formulas are shown in the table below: ;

[0041] By constraining the intersection, we can determine that 208.5°≤θ≤210°. Within this interval, we take the middle value and round it to obtain a central angle of 209°.

[0042] Example 2 See Figure 1 As shown, this embodiment follows the design results of Embodiment 1 to prepare a transparent conductive film, as detailed below.

[0043] Step 1: Conductive Seed Layer Deposition. A clean glass substrate (or rigid substrate such as glass, silicon wafer, or metal sheet) is used. A 120 nm thick nickel (Ni) metal film is deposited on its surface via electron beam evaporation. Deposition parameters: Vacuum level better than 3 × 10⁻⁶. -3 The deposition rate is approximately 0.5 Å / s. This Ni film has a dual function: firstly, it is a conductive seed layer that ensures uniform current distribution in subsequent electroplating steps, allowing for uniform copper deposition within the photoresist trenches; secondly, it is a lift-off control layer that enables mechanical lift-off by controlling the PDMS / Ni interface adhesion, eliminating the need for chemical etching.

[0044] A 120 nm thick Ni layer is used as a conductive seed layer for electroplating. During the transfer stage, the interfacial bonding force between PDMS and the Ni layer is controlled to achieve mechanical peeling of the Ni layer. This eliminates the need for a multilayer film structure, simplifies the process, and avoids the pollution and selective etching control problems introduced by chemical etching.

[0045] Step 2: Preparation of a 209° central angle circular arc serpentine pattern photomask. A two-stage spin coating process is used to uniformly coat the Ni layer surface with JZJ-550M-50cp positive photoresist: First stage: Spin coating at 500 rpm for 6 seconds.

[0046] Second stage: Spin coating at 1000 rpm for 27 seconds, resulting in a photoresist thickness of approximately 5 μm. Pre-bake at 100°C for 150 seconds. Perform UV exposure using a chrome mask with a 209° central angle circular arc serpentine pattern (circumference R can be selected as 50 / 200 / 350 μm), exposing the underlying Ni layer with a trench width and depth of approximately 5 μm.

[0047] Step 3: In-situ electrochemical deposition of copper micromesh. A substrate with a photoresist mask is used as the cathode, and a Cu plate as the anode. The substrate is placed in an electroplating bath for constant current electroplating. By applying an electric field and controlling the electroplating time and conditions (0.01A / 0.02A / 0.03A) (25mins / 50mins / 75mins), copper grows in-situ within the photoresist trenches, with a line thickness of approximately 6 μm, comparable to the photoresist thickness, forming a precise 209° central angle circular arc serpentine copper micromesh. The copper micromesh is flat and uniform, without overflow or breakage.

[0048] Step 4: Photoresist removal. Immerse the electroplated sample in 60°C NMP for about 90 seconds, then immerse it in ethanol for about 30 seconds. Blow it dry with a nitrogen gun to remove the photoresist mask. At this point, the formed serpentine copper network structure is clearly visible on the nickel layer.

[0049] Step 5: Elastomer Encapsulation. Dow Corning Sylgard 184 PDMS prepolymer and curing agent are thoroughly mixed at a 10:1 (mass ratio) and degassed. The mixture is then uniformly poured onto the surface of the copper micromesh at a areal density of 15 mg / cm², ensuring the liquid PDMS completely fills the gaps between the copper wires and three-dimensionally encapsulates the copper micromesh. The mixture is then cured on a 60°C heating plate for 3 hours, causing the liquid PDMS to crosslink into a solid elastomer. The serpentine copper micromesh is then firmly anchored three-dimensionally within the PDMS matrix, forming an integral composite structure.

[0050] Step 6: Non-destructive transfer based on mechanical exfoliation. After curing, the edge of the PDMS / copper composite layer is gently pried up with tweezers, and uniform force is applied along the direction parallel to the substrate to mechanically peel the entire composite layer from the glass / Ni substrate. Part of the Ni layer remains on the bottom surface of the PDMS, and part remains on the glass surface, achieving complete non-destructive transfer of the copper / PDMS composite electrode. A stretchable transparent conductive film with a 209° central angle topology is obtained.

[0051] Figure 2a Different structural features of the conductive layer are shown. Figure 2b The radar image shows a performance comparison of conductive layer patterns of 180° serpentine, sinusoidal, and 209° serpentine. It clearly shows that the 209° serpentine pattern, with a radius of 50 micrometers, offers the best overall performance (the sheet resistance and resistivity changes are expressed in reciprocals for a more intuitive comparison of area). Figure 2c , Figure 2d The transmittance of the three structural patterns in the 330-1000nm wavelength range and the resistivity after 300 cycles of cyclic stretching at 20% strain were compared, which intuitively demonstrated the performance advantages of the 209° central angle serpentine shape.

[0052] After 300 cycles at 20% strain, the 209° circular arc structure has a ΔR / R ≤ 0.1, which is about 7 times higher than that of the 180° circular arc (ΔR / R0 ≈ 0.7) and more than 30 times higher than that of the sine wave (ΔR / R0 > 2.8).

[0053] Figure 3a The diagrams show three different circular arc radii (R) with a 209° central angle serpentine structure design. Figure 3b Normalized resistance change (ΔR / R0) curves of 209° central angle TCEs with three arc radii under 1500 cycles of tensile stress at 20% tensile strain are presented. These results confirm the significant advantage of the 209° central angle design in terms of cyclic tensile stability, and large-scale structures exhibit the best cyclic stability due to fewer geometric stress points per unit area, fewer microcracks, and a more uniform strain distribution. Figure 3cThe photoelectric properties (sheet resistance Rs vs transmittance T@550nm) of TCEs with three different arc radii and a central angle of 209° were compared. The bar chart clearly shows that as the arc radius increases, the transmittance increases significantly, while the sheet resistance remains relatively stable. Figure 3d The optical transmittance curves of TCEs with three arc radii and a central angle of 209° are shown in the wavelength range of 330–1000 nm. The curves clearly show that the large-scale structure with R = 350 μm maintains a transmittance of over 90% across the entire visible light range, reaching approximately 92% at 550 nm, which is close to the transmittance level of ITO thin films (>90%). Figure 3e A scanning electron microscope image of a large-scale 209° central angle serpentine copper micromesh with R = 350 μm is shown.

[0054] Figure 4a and Figure 4b The uniformity of the prepared 209° centered-angle serpentine copper micromesh transparent conductive film was demonstrated, confirming that the preparation process of this invention has excellent large-area uniformity and repeatability. Figure 4c As can be seen, the 209° central angle TCEs (R = 350 μm) were used as conductive connecting wires in a practical application demonstration of lighting up LEDs under different tensile strains (0%, 20%, 40%, 60%). This verifies the practical reliability of the 209° central angle design under large strain. Figure 4d The normalized resistance change (ΔR / R0) of TCEs with a central angle of 209° (R = 200 μm) under different tensile strains of 20%, 30%, 40%, and 50% is shown as a function of the number of tensile cycles. This demonstrates that the TCEs design exhibits excellent cyclic stability under moderate strain (≤30%), meeting the practical application requirements of most flexible electronic devices. Figure 4e , 4f This reflects the long-cycle bending and tensile stability test of the present invention. The resistance change during the bending process remained within ±1% throughout the entire 10,000 cycles. During the entire 5,000 tensile cycles, ΔR / R0 showed a slow upward trend, gradually increasing from the initial 0 to about 0.18. These data further verified the ultra-long-cycle stability of the 209° central angle design under medium-high strain (20%), and confirmed its high reliability in practical applications. Figure 4g The normalized resistance change (ΔR / R0) curves of 209° central angle TCEs (R = 200 μm) prepared under different electroplating times (25 min, 50 min, 75 min) after 1500 cycles of tensile testing at 20% strain are shown. The curves clearly show that the copper micromesh thickness (electroplating time) is a crucial parameter affecting cycle stability.

[0055] Figure 5a Large-area scanning electron microscope (SEM) images of a 209° centered serpentine copper micromesh fabricated and transferred onto a PDMS substrate are presented. The serpentine copper micromesh exhibits high periodicity and regularity within its periodic range, with smooth transitions between the 209° arc segments and straight segments, without obvious breaks, wrinkles, or localized detachment. Similarly, images 5b and 5c show that the copper wires exhibit an approximately trapezoidal cross-sectional shape, with a width of approximately 5 μm and a thickness of approximately 6 μm (corresponding to an electroplating time of 75 min), and are completely embedded in the PDMS substrate. This "embedded" structural design significantly enhances the mechanical interlocking effect between the copper micromesh and the flexible substrate, preventing resistance increases or structural failure due to interfacial peeling during cyclic stretching. Figure 5d X-ray diffraction (XRD) patterns of the electroplated copper micromesh are shown. The patterns clearly show three distinct diffraction peaks located at 2θ = 43.3°, 50.4°, and 74.1°, corresponding to the (111), (200), and (220) crystal planes of the face-centered cubic (FCC) crystal structure of copper. The (111) peak, with the highest intensity, is the dominant peak, indicating that the electroplated copper film has a (111) preferred orientation. This orientation typically corresponds to higher electrical conductivity and better mechanical ductility. No obvious copper oxide (CuO or Cu2O) characteristic peaks were observed, indicating that the copper micromesh did not undergo significant oxidation during preparation and storage, maintaining good chemical stability. Finally... Figure 5e The morphology of the circulating unit of the copper microgrid is shown. Figures 5f-5i The EDX elemental distribution map shown confirms that copper exists only in the serpentine region, while silicon (representing the PDMS matrix) fills the gaps between the copper microgrids, with no obvious overlap or mixing areas. This clear interface confirms that the interfacial bonding between the copper microgrids and the PDMS substrate is tight but chemically independent, with no obvious interdiffusion or reaction products.

[0056] In other embodiments, the Ni layer thickness can be adjusted to 50–200 nm; the seed layer material can also be replaced with Cr (thickness 20–50 nm), and step five is changed to chemical stripping by injecting from the edge with an HF-based etching solution (HF:H2O=1:10), which is suitable for scenarios where mechanical stripping force cannot be applied to large-area films; the central angle of the arc-shaped serpentine structure can be adjusted in the range of 180°–270°, preferably 209°; the arc radius R can be adjusted in the range of 50–350 μm; the elastomer can be replaced with Ecoflex 00-30 (A:B=1:1, room temperature curing for 4 h), SEBS, or TPE, which is suitable for ultra-low modulus bionic skin applications; copper can be replaced with a Cu-Ni-Au three-layer structure to improve oxidation resistance; a variety of feasible alternatives can achieve the same purpose.

[0057] It should be understood that the above embodiments are merely illustrative of the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A serpentine metal-elastomer composite transparent conductive film, characterized in that, The invention includes a transparent elastomer film and an embedded metal mesh. The embedded metal mesh comprises a plurality of crisscrossing first serpentine lines and a plurality of second serpentine lines. Both the first and second serpentine lines are composed of alternating semi-circular arcs arranged on both sides of a centerline, and the intersection of the first and second serpentine lines is the endpoint of the semi-circular arc.

2. The serpentine metal-elastomer composite transparent conductive film according to claim 1, characterized in that, The central angle of the super semicircular arc is 180-270°; And / or, the radius of the super-semicircular arc is 50-350μm.

3. The serpentine metal-elastomer composite transparent conductive film according to claim 2, characterized in that, The constraints on the geometric properties of the embedded metal mesh include: Interface stripping constraints: (E_m·t·ε0 2 ) / (E_s·t_s·2.16)·sin 2 (θ / 2)·[1+cos 2 (θ / 2)]·[1+0.25·K_stress(θ)]≤8·G_c; Fatigue stability constraints: 2·ε0·sin 2 (θ / 2)·[1+K_stress(θ) / 10]·K_stress(θ)<6.0; Geometric constraints: 180° < θ < 270°; Resistance constraint: ρ·L_eff / (w·t)≤100Ω; Fatigue life constraints: N_f(θ)≥10 4 ; in: K_stress(θ)=1+2.8·|sin(θ-180°)|^1.5·[1+0.45·(t / w)^0.6]·[1+0.08·(E_m / E_s)^0.3]; G_IC,plastic(θ)=(E_m·t·ε0²) / (E_s·t_s·2.16)·sin²(θ / 2)·[1+cos²(θ / 2)]·[1+0.25·K_stress(θ)]; L_eff(θ) / L0=2(πR·α / 180°+l) / (2R+2l), R=w / [2·sin(α / 2)], α=θ-180°; N_f(θ)=8×10 5 ·[Δε_eff(θ)]^(-1.8), Δε_eff(θ)=2·ε0·sin²(θ / 2)·[1+K_stress(θ) / 10]; E_m represents the elastic modulus of the embedded metal mesh, t represents the thickness of the first and second serpentine lines, ε0 represents the design strain, E_s represents the elastic modulus of the transparent elastomer film, t_s represents the thickness of the transparent elastomer film, θ represents the central angle, α represents the deflection angle, K_stress(θ) represents the stress concentration factor, G_c represents the interfacial fracture energy, ρ represents the resistivity of the embedded metal mesh, G_IC,plastic(θ) represents the interfacial energy release rate related to the central angle, L_eff represents the effective tensile length, L0 represents the straight length of the serpentine lines, w represents the planar pattern width of the first and second serpentine lines, N_f represents the fatigue life, and Δε_eff represents the effective strain amplitude.

4. The serpentine metal-elastomer composite transparent conductive film according to claim 1, characterized in that, The material of the embedded metal mesh includes any one or a combination of two or more of Cu, Au, and Ni.

5. The serpentine metal-elastomer composite transparent conductive film according to claim 1, characterized in that, The material of the transparent elastomer film includes any one or a combination of two or more of PDMS, PBAT, SEBS, and TPE.

6. A method for designing a serpentine metal-elastomer composite transparent conductive film according to any one of claims 1-5, characterized in that, include: The range of central angle values ​​for the serpentine lines in the serpentine metal-elastomer composite transparent conductive film is determined by using constraints, including: Interface stripping constraints: (E_m·t·ε0 2 ) / (E_s·t_s·2.16)·sin 2 (θ / 2)·[1+cos 2 (θ / 2)]·[1+0.25·K_stress(θ)]≤8·G_c; Fatigue stability constraints: 2·ε0·sin 2 (θ / 2)·[1+K_stress(θ) / 10]·K_stress(θ)<6.0; Geometric constraints: 180° < θ < 270°; Resistance constraint: ρ·L_eff / (w·t)≤100Ω; Fatigue life constraints: N_f(θ)≥10 4 ; in: K_stress(θ)=1+2.8·|sin(θ-180°)|^1.5·[1+0.45·(t / w)^0.6]·[1+0.08·(E_m / E_s)^0.3]; G_IC,plastic(θ)=(E_m·t·ε0²) / (E_s·t_s·2.16)·sin²(θ / 2)·[1+cos²(θ / 2)]·[1+0.25·K_stress(θ)]; L_eff(θ) / L0=2(πR·α / 180°+l) / (2R+2l), R=w / [2·sin(α / 2)], α=θ-180°; N_f(θ)=8×10 5 ·[Δε_eff(θ)]^(-1.8), Δε_eff(θ)=2·ε0·sin²(θ / 2)·[1+K_stress(θ) / 10]; E_m represents the elastic modulus of the embedded metal mesh, t represents the thickness of the first and second serpentine lines, ε0 represents the design strain, E_s represents the elastic modulus of the transparent elastomer film, t_s represents the thickness of the transparent elastomer film, θ represents the central angle, α represents the deflection angle, K_stress(θ) represents the stress concentration factor, G_c represents the interfacial fracture energy, ρ represents the resistivity of the embedded metal mesh, G_IC,plastic(θ) represents the interfacial energy release rate related to the central angle, L_eff represents the effective tensile length, L0 represents the straight length of the serpentine lines, w represents the planar pattern width of the first and second serpentine lines, N_f represents the fatigue life; Δε_eff represents the effective strain amplitude. Within the range of values, the final value of the central angle is determined.

7. The design method according to claim 6, characterized in that, Specifically, it includes: Obtain the median value of the range; The intermediate value is rounded to obtain the final value.

8. A method for preparing a serpentine metal-elastomer composite transparent conductive film according to any one of claims 1-5, characterized in that, include: A metal seed layer is set on the substrate surface; A patterned mask layer is disposed on the surface of the metal seed layer, the pattern of the mask layer being complementary to the pattern of the embedded metal mesh; The embedded metal mesh is formed by depositing on the metal seed layer exposed in the mask layer using electrochemical deposition. Remove the mask layer, and cast and cure to form a transparent elastomer film; The transparent elastomer film and the serpentine metal-elastomer composite transparent conductive film formed by the embedded metal mesh are peeled off from the metal seed layer.

9. The preparation method according to claim 8, characterized in that, Specifically, it includes: The serpentine metal-elastomer composite transparent conductive film is mechanically peeled off from the metal seed layer; Alternatively, an etchant can be dropped onto the edge of the serpentine metal-elastomer composite transparent conductive film and the metal seed layer for chemical stripping.

10. The application of the serpentine metal-elastomer composite transparent conductive film according to any one of claims 1-5 in the fabrication of wearable smart devices, flexible displays, biomimetic electronic skin, and implantable biomedical devices.